2015
DOI: 10.1002/2014ea000059
|View full text |Cite
|
Sign up to set email alerts
|

Experimental dissolution of molybdenum‐sulphides at low oxygen concentrations: A first‐order approximation of late Archean atmospheric conditions

Abstract: The abundance of atmospheric oxygen and its evolution through Earth's history is a highly debated topic. The earliest change of the Mo concentration and isotope composition of marine sediments are interpreted to be linked to the onset of the accumulation of free O 2 in Earth's atmosphere. The O 2 concentration needed to dissolve significant amounts of Mo in water is not yet quantified, however. We present laboratory experiments on pulverized and surface-cleaned molybdenite (MoS 2 ) and a hydrothermal breccia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The riverine flux of Re is assumed to have become largely independent of atmospheric O 2 levels at the early stage of the GOE, when atmospheric O 2 levels rose above the threshold (as low as <0.001% PAL) required to support subaerial oxidative dissolution of crustal sulfide minerals and delivery of the related products to the oceans Anbar et al, 2007;Reinhard et al, 2013b;Greber et al, 2015). Details of these assumptions await further study, particularly weathering relationships.…”
Section: Anoxic Sinkmentioning
confidence: 99%
See 1 more Smart Citation
“…The riverine flux of Re is assumed to have become largely independent of atmospheric O 2 levels at the early stage of the GOE, when atmospheric O 2 levels rose above the threshold (as low as <0.001% PAL) required to support subaerial oxidative dissolution of crustal sulfide minerals and delivery of the related products to the oceans Anbar et al, 2007;Reinhard et al, 2013b;Greber et al, 2015). Details of these assumptions await further study, particularly weathering relationships.…”
Section: Anoxic Sinkmentioning
confidence: 99%
“…Molybdenum abundances in stage 2 and 3 ORM, which are far more sensitive specifically to the extent of ocean euxinia rather than general anoxia compared with other redox-sensitive metals, are intermediate between those seen in Archean and Phanerozoic ORM (Scott et al, 2008;Sahoo et al, 2012;Reinhard et al, 2013a). The lack of S-MIF in stage 3 sedimentary rocks indicates that atmospheric O 2 levels were high enough to support persistent oxidative mobilization of Re via weathering of crustal sulfide minerals and organic matter (Reinhard et al, 2013b;Planavsky et al, 2014;Greber et al, 2015;Cole et al, 2016). Hence, the drop in authigenic Re enrichments during stage 3 likely reflects an expansion of global ocean anoxia rather than a decline in the riverine Re flux.…”
Section: Temporal Trends In Re Concentrationsmentioning
confidence: 99%
“…While Mo may behave as a chalcophile element in euxinic sedimentary and low-temperature hydrothermal environments, its behavior during igneous differentiation and crust formation is less well understood. Newsom and Palme (1984) suggested that Mo will behave incompatibly during mantle melting, like Ce and Pr, and this is corroborated by the observation that Mo is significantly enriched in the UCC (1.1 µg/g; Rudnick and Gao, 2014) relative to the primitive mantle (0.039 -0.047 µg/g; Greber et al, 2015aGreber et al, , 2015bPalme and O'Neill, 2004, respectively). Moreover, Mo is observed to behave incompatibly during differentiation of intraplate basalt magmas (Yang et al, 2015;Greaney et al, 2017).…”
Section: Molybdenum As a Redox Proxymentioning
confidence: 78%
“…Additionally, Wille et al (2018) suggest that Mo isotopes may be fractionated during crystallization of amphibole or clinopyroxene in arc settings. Overall, a net isotope fractionation is observed between average UCC felsic rocks ($+0.15‰; Willbold and Elliott, 2017) and MORB ($0.0‰; Liang et al, 2017;Bezard et al, 2016) and OIB ($À0.14‰; Liang et al, 2017), suggesting that not only [Mo] but also Mo isotopes may be fractionated during igneous differentiation (Voegelin et al, 2014;Yang et al, 2017;Liang et al, 2017;Greber et al, 2015aGreber et al, , 2015bWille et al, 2018). By contrast, other studies show that Mo abundances and isotopes are not significantly fractionated by differentiation processes in intraplate and arc settings (Yang et al 2015;Gaschnig et al, 2017aGaschnig et al, , 2017b.…”
Section: Hypothesis 1: Loss Of Mo Due To Partitioning Into Titaniferomentioning
confidence: 99%
See 1 more Smart Citation